Sterowanie konsumpcją w okresach przyspieszania i zwalniania wzrostu gospodarczego - Woś, Jerzy (Wydział Prawa i Administracji UAM, 1986)
The task of the article is a study of a consumption policy, its substance, targets and basic conditioning in the real economic environment. Particularly it is the case of presenting results of certain variants of consumption policy in the period of accelerated and impeded economic growth. Defining the essence of consumption policy in the socialist economy and the attempt at generating models of the consumption policy are the departure point. It is established in the result of the discussion that in the initial acceleration phase the consumption policy adopts a motivational character and results in a formation of a motivational consumption model, on account of limiting the inflow of means to the branch II in the second acceleration phase,, the incentive power of consumption considerably decreases and the consumption model adopts more and more the features on the unbalanced one. In the final acceleratiomal phase and in the initial period of the impeded growth the unbalanced model is finally formed and it can adopt features of reproductioinal model subject to the degree of market disequilibrium. Throughout all the periods we have to deal with market disequilibrium, in the period of motivational model it is shallow and becomes aggravated during the reproductional model period, and may end up with a regulated sale of consumptional goods.
Controlling the Consumption in the Periods of Accelerated and Impeded Economic Growth